2017
DOI: 10.1111/psyp.12880
|View full text |Cite
|
Sign up to set email alerts
|

Emotional self–other voice processing in schizophrenia and its relationship with hallucinations: ERP evidence

Abstract: Abnormalities in self-other voice processing have been observed in schizophrenia, and may underlie the experience of hallucinations. More recent studies demonstrated that these impairments are enhanced for speech stimuli with negative content. Nonetheless, few studies probed the temporal dynamics of self versus nonself speech processing in schizophrenia and, particularly, the impact of semantic valence on self-other voice discrimination. In the current study, we examined these questions, and additionally probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 71 publications
2
21
0
Order By: Relevance
“…Interestingly, a recent study (Pinheiro et al, 2018) testing non-clinical voice hearers using a similar setup as the first experiment in the current study, also using natural vowel sounds, showed that the N1-supression effect is reversed in non-clinical voice hearers with high symptom scores compared to those with low symptom scores whereas the P2-supression effect is maintained in both groups. This is in accordance with findings in schizophrenia patients (Ford, et al, 2014) using a similar paradigm, which indicates that alterations in generating motor-toauditory predictions might be linked to developing auditory hallucinations (Brebion et al, 2016;Pinheiro et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, a recent study (Pinheiro et al, 2018) testing non-clinical voice hearers using a similar setup as the first experiment in the current study, also using natural vowel sounds, showed that the N1-supression effect is reversed in non-clinical voice hearers with high symptom scores compared to those with low symptom scores whereas the P2-supression effect is maintained in both groups. This is in accordance with findings in schizophrenia patients (Ford, et al, 2014) using a similar paradigm, which indicates that alterations in generating motor-toauditory predictions might be linked to developing auditory hallucinations (Brebion et al, 2016;Pinheiro et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, a prediction error may arise from the comparison of a less specific/accurate prediction with the available sensory feedback. A less specific prediction may imply altered self-monitoring of speech, which has been consistently associated with AVH 34 , 36 , 37 , 59 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Before Experiment 2, a voice recording session took place: participants were instructed to repeatedly vocalize the syllable “ah”. Recordings were made with an Edirol R-09 recorder and CS-15 cardioid-type stereo microphone 37 , 45 . After the recording, the best voice sample of the vowel /a/ from each participant (i.e., constant prosody; maximum duration of 300 ms) was selected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advantages of high temporal resolution and direct measure of neural activity, event-related potential (ERP) is an ideal methodology for exploring the dynamical temporal features of cognitive processing (Graux et al., 2013, 2015; Pinheiro et al., 2016, 2017). A growing number of ERP studies have provided evidences of the self-relevant effect.…”
Section: Introductionmentioning
confidence: 99%